Парламентський контроль у системі державного управління в Україні - Козар, Ю.; Kozar, Yu.; Гаріфуллін, М. В.; Harifullin, M. V. (Науковий вісник Дніпропетровського державного університету внутрішніх справ. – 2022. – № 2. – С. 51-57, 2022)
Досліджено законодавство, наукові розробки для розкриття основних елементів парламентського контролю у сфері публічного управління в Україні, визначено основні проблеми та тенденції розвитку цього питання. Зазначено, що основною метою цього виду контролю є здійснення регулювання діяльності органів управління, визначення основних недоліків та перешкод на шляху до реалізації ефективного виконання органами публічного управління своїх функцій та усунення цих перешкод. Акцентовано на тому, що парламентський контроль у сфері публічного управління є недостатньо вивченим та здійснено спробу його подальшого вдосконалення.

The question of the parliamentary control in the sphere of public administration in Ukraine is very important and actual today. The main problem of the parliamentary control as the social phenomenon exists and must have the ways of the solution. During the adoption of laws, the parliament must exercise the control function for the authority of public administration as for the question of the implementation of laws, and the parliament must reveal the shortcomings and the obstacles in the implementation of laws by the authority of public administration. The parliamentary control it is designed to create the conditions that will be appropriate for the realization of laws by management bodies, and is also designed to create the conditions of the functioning of all system of executive bodies, its structures and the members of governing bodies. The parliamentary control forthe public administration must be exercised within the principle of legality and the division of powers. So, in accordance with the principle of legality and the division of powers, parliament must receive all proper information about the real state of the work of the authority of public administration, about the state of the implementation of their powers, and in case of the appearance of the problems in the activity of these bodies, it must provide the appropriate conditions and it must influence their activities. This means that the parliamentary control in the sphere of public administration must have the certain methods and the ways of the influence, by means of which it will be able to carry out its control function in this sphere and it will provide the realization of citizens' rights. The research of the parliamentary control is important and actual in both theoretical and practical meanings. The purpose of the research is to explore the legislation, the scientific visions for disclosure of the main elements of the parliamentary control in the sphere of public administration in Ukraine, the definition of the main problems and the tendency of the development of this question.

Досліджено законодавство, наукові розробки для розкриття основних елементів парламентського контролю у сфері публічного управління в Україні, визначено основні проблеми та тенденції розвитку цього питання. Зазначено, що основною метою цього виду контролю є здійснення регулювання діяльності органів управління, визначення основних недоліків та перешкод на шляху до реалізації ефективного виконання органами публічного управління своїх функцій та усунення цих перешкод.
Parliamentary control in the system of public administration in Ukraine
Keywords: контроль; control; парламентський контроль; parliamentary control; парламентский контроль; публічне управління; public administration; публичное управление; державне управління; governance; государственное управление; принципи парламентського контролю; principles of parliamentary control; принципы парламентского контроля